Gastrointestinal Dysfunction Impact on Life Quality in a Cohort of Russian Patients with Parkinson’s Disease I-III H&Y Stage - A. A. Pilipovich; O. V. Vorob’eva; S. A. Makarov; N. N. Shindryaeva; Yu D. Vorob’eva (Parkinson's Disease)
Background. There are still no clearly proven methods to slow down or stop the progression of Parkinson’s disease (PD). Thus, improving the quality of life (QoL) of patients with PD becomes of primary importance. Autonomic dysfunction and its symptoms are known to worsen the quality of life in PD, but the degree of this influence is underinvestigated. Particularly, impacts of the separate significant gastrointestinal symptoms, such as dyspepsia, constipation, and abdominal pain, in PD should be more precisely evaluated with the help of specific scales. Objective. To assess the impacts of gastrointestinal dysfunction and its symptoms on PD patient’s QoL using PDQ-39. Methods. 111 PD patients in the I-III Hoehn and Yahr (H&Y) stage were enrolled in the study. The following scales were applied: UPDRS III, PDQ-39, GSRS, GDSS, MMSE, BDI, STAI-S, and STAI-T. Results. The linear regression model showed that the PDQ-39 SI depended on summary assessments GSRS-SI (β = 0.333, p<0.001), BDI (β = 0.463, p<0.001), and UPDRS III (β = 0.163, p<0.05). The use of the stepwise method, adding GSRS-SI and UPDRS III scores to the BDI predictor, improved the model (R2 increased from 0.454 to 0.574). The investigation of GSRS domain’s influence revealed that PDQ-39 SI had a significant correlation with almost all of them, but the regression analysis showed significant QoL impacts of only two factors: constipation and abdominal pain (β = 0.288, p<0.01 and β = 0.243, p<0.05 accordingly). Conclusions. Our results suggest a considerable negative influence of depression and gastrointestinal dysfunction (especially constipation and abdominal pain) on QoL of patients with PD. Their impact on QoL in patients with I-III H&Y stages of PD is more significant than that of motor symptoms. Therefore, the correction of depression and gastrointestinal dysfunction should be prioritized in PD therapy.